An Overview of the Role of Innate Lymphoid Cells in Gut Infections and Inflammation - Silvia Sedda; Irene Marafini; Michele M. Figliuzzi; Francesco Pallone; Giovanni Monteleone (Hindawi Limited, 2014)
Innate lymphoid cells (ILCs) are a group of hematopoietic cells devoid of antigen receptors that have important functions in lymphoid organogenesis, in the defense against extracellular pathogens, and in the maintenance of the epithelial barrier. Three distinct groups of ILCs have been identified on the basis of phenotypic and functional criteria and termed ILCs1, ILCs2, and ILCs3. Specifically, ILCs1 express the transcription factor T-bet and secrete T helper type-1- (Th1-) related cytokines, ILCs2 are dependent on the transcription factor RORα and express Gata-3 and the chemokine receptor homologous molecule (CRTH2) and produce Th2-related cytokines, and ILCs3 express the transcription factor RORγt and synthesize interleukin- (IL-) 17, IL-22, and, under specific stimuli, interferon-γ. ILCs represent a relatively small population in the gut, but accumulating evidence suggests that these cells could play a decisive role in orchestrating both protective and detrimental immune responses. In this review, we will summarize the present knowledge on the distribution of ILCs in the intestinal mucosa, with particular focus on their role in the control of both infections and effector cytokine response in immune-mediated pathologies.